The molecular mechanism of phytosphingosine binding to FFAR4/GPR120 differs from that of other fatty acids. Issue 11 (3rd October 2021) - Nagasawa, Tomotaka; Horitani, Masaki; Kawaguchi, Shin‐ichi; Higashiyama, Shigeki; Hama, Yoichiro; Mitsutake, Susumu
Abstract : Free fatty acid receptor 4 (FFAR4)/GPR120 comprises a receptor for medium‐ and long‐chain fatty acids. We previously identified phytosphingosine (PHS) as a novel ligand of FFAR4. Although many natural FFAR4 ligands have carboxyl groups, PHS does not, thus suggesting that binding to FFAR4 is driven by a completely different mechanism than other natural ligands such as α‐linolenic acid (ALA). To test this hypothesis, we performed docking simulation analysis using a FFAR4 homology model based on a protein model derived from the crystal structure of activated turkey beta‐1 adrenoceptor. The docking simulation revealed that the probable hydrogen bonds to FFAR4 differ between various ligands. In particular, binding was predicted between R264 of the FFAR4 and the oxygen of the carboxylate group in ALA, as well as between E249 of the FFAR4 and the oxygen of the hydroxy group at the C4‐position in PHS. Alanine substitution at E249 (E249A) dramatically reduced PHS‐induced FFAR4 activation but demonstrated a weaker effect on ALA‐induced FFAR4 activation. Kinetic analysis and K m values clearly demonstrated that the E249A substitution resulted in reduced affinity for PHS but not for ALA. Additionally, we observed that sphingosine, lacking a hydroxyl group at C4‐position, could not activate FFAR4. Our data show that E249 of the FFAR4 receptor is crucial for binding to the hydroxy group at the C4‐position in PHS, and this is a completely different molecular mechanism of binding from ALA. Because GPR120 agonists have attracted attention as treatments for type 2 diabetes, our findings may provide new insights into their development. Abstract : Free fatty acid receptor 4 (FFAR4)/GPR120 is known as a receptor for medium‐ and long‐chain fatty acids. We previously identified phytosphingosine (PHS) as a novel ligand of FFAR4. The present study demonstrated that E249 of the FFAR4 receptor is crucial for binding to the hydroxy group at the C4‐position in PHS, and this is a completely different molecular mechanism of binding from α‐linolenic acid.